Simultaneous Production of Hydrogen Peroxide and Bioelectricity Generation at the Cathode Using Modified Graphite Electrodes - Montenegro-Rosero, K (Elsevier Ltd, 2025)
This study introduces an innovative strategy to enhance hydrogen peroxide (H₂O₂) production and wastewater treatment in bioelectrochemical systems (BES). Graphite cathodes were modified by electrospinning polymer-based nanofibers doped with iron oxide nanoparticles onto their surface, which substantially improved their electrocatalytic properties and increased the electroactive surface area by 50 %. In single-compartment electrochemical cells, the modified electrodes achieved a maximum H₂O₂ concentration of 0.83 mM, representing a fivefold increase compared with unmodified graphite. The BES exhibited excellent performance in both heterotrophic denitrification and H₂O₂ generation. Microbial fuel cells (MFCs) achieved complete nitrate removal within 8 h, while microbial electrolysis cells (MECs) reached 72.7 % removal in the same period. After 24 h, both systems attained complete nitrate removal and a 95 % reduction in chemical oxygen demand (COD). Power and current densities of 4.39 ± 0.07 mW m⁻² and 16.56 ± 0.16 mA m⁻², respectively, underscored the potential of these systems for simultaneous energy recovery and wastewater treatment. In MECs, the maximum H₂O₂ concentration reached 93.16 ± 2.8 mg L⁻¹ —up to 18 times higher than levels typically required for environmental applications such as disinfection and removal of emerging contaminants. Overall, these findings demonstrate the effectiveness of modified graphite electrodes in ecological biotechnology and highlight their promise for advancing sustainable wastewater treatment technologies. © 2025 Elsevier Ltd.